1999
DOI: 10.1016/s0304-3959(98)00152-3
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of N -Methyl-D-aspartate receptor blockade on nociceptive somatic and visceral reflexes

Abstract: N-methyl-D-aspartate (NMDA) receptors appear to play little part in nociceptive responses evoked by acute stimulation of normal somatic tissues, but rather are involved in hyperalgesic responses after peripheral injury and inflammation. Previous studies from this laboratory have shown important differences in the neural organization of somatic and visceral nociceptive pathways. Here, we have explored the role of NMDA receptors in processing acute visceral noxious input, compared with somatic noxious input. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 30 publications
2
42
0
Order By: Relevance
“…These findings are in agreement with those of previous studies (Poynard et al, 1994;Maxton et al, 1996). Other candidate receptors known to be associated with visceral pain are tachykinin NK 2 , calcitonin gene-related peptide, and N-methyl-D-aspartate receptors (McLean et al, 1997;Plourde et al, 1997;Olivar and Laird, 1999); however, further studies will be required to clarify the involvement of these receptors in the viscerosensory responses caused by colorectal distention in rabbits.…”
supporting
confidence: 90%
“…These findings are in agreement with those of previous studies (Poynard et al, 1994;Maxton et al, 1996). Other candidate receptors known to be associated with visceral pain are tachykinin NK 2 , calcitonin gene-related peptide, and N-methyl-D-aspartate receptors (McLean et al, 1997;Plourde et al, 1997;Olivar and Laird, 1999); however, further studies will be required to clarify the involvement of these receptors in the viscerosensory responses caused by colorectal distention in rabbits.…”
supporting
confidence: 90%
“…46;55-56 Visceral nociceptive responses have greater sensitivity to peripherally administered NMDAR antagonists than those arising from somatic tissues implying a greater role of these NMDARs in visceral pain transmission. [57][58] In peripheral tissue, stimulation of NMDARs causes release of the neuropeptides like substance P (SP) and calcitonin gene-related peptide (CGRP) from capsaicin-sensitive peripheral nerve terminals. 57 These neuropeptides and growth factors contribute to neurogenic inflammation.…”
Section: Aromatasementioning
confidence: 99%
“…Spinal administration of NMDAR agonists has dose-dependently facilitated the visceromotor reflex, together with pressor responses to pelvic noxious stimulation (14). Conversely, blockage of NMDAR using pharmacological antagonists has inhibited pain behavior caused by irritation of the pelvic viscera (24,43). Among subunits of NMDAR, the role of the NR2B subunit in pain development has been intensively investigated, as electrophysiological studies have demonstrated that phosphorylation of specific NR2B tyrosine residues is an important determinant for NMDAR-mediated currents (22), which defines the role of NMDARs in pain-related neural plasticity (3,17,18,20).…”
mentioning
confidence: 99%